The Effect Of Counseling With Video Media On Parental Knowledge In Preventing Diarrhea In Toddlers In The Working Area Of The Lubuk Sanai Health Center, Mukomuko Regency, 2022 - Yunita, Nourma (Student Scientific Journal, 2023)
Diarrheal disease can be prevented by using water for hygiene and clean water for drinking, washing hands, defecating in the latrines and using latrines must be maintained by washing them regularly, disposing of children's feces properly, immunizing against measles as soon as possible (WHO, 2012). The purpose of this study was to find out the effect of counseling with video media on parents' knowledge in preventing diarrhea at the Lubuk Sanai Health Center, Mukomuko Regency in 2022. This research is a research using a quasi-experimental design with a pretest-posttest one group design approach. The study population consisted of all 191 patients with diarrhea, the sample was 30 patients. The sampling technique used in this study was accidental sampling. Data analysis techniques using the Dependent T Test. The results of this study show that there are differences before and after counseling with video media, namely the mean before 37 and the mean after 82.33 and the p-value is 0.00, it can be concluded that there is an effect of providing video education on parental knowledge on preventing diarrhea in toddlers at the Lubuk Sanai Health Center, Mukomuko Regency in 2022. Suggestions in this study are expected for researchers who are expected to be able to use other research variables that are more specific by looking at the influence of variables such as work, age and experience of the mother and increasing the number of samples. Diarrheal disease can be prevented by using water for hygiene and clean water for drinking, washing hands, defecating in the latrines and using latrines must be maintained by washing them regularly, disposing of children's feces properly, immunizing against measles as soon as possible (WHO, 2012). The purpose of this study was to find out the effect of counseling with video media on parents' knowledge in preventing diarrhea at the Lubuk Sanai Health Center, Mukomuko Regency in 2022. This research is a research using a quasi-experimental design with a pretest-posttest one group design approach. The study population consisted of all 191 patients with diarrhea, the sample was 30 patients. The sampling technique used in this study was accidental sampling. Data analysis techniques using the Dependent T Test. The results of this study show that there are differences before and after counseling with video media, namely the mean before 37 and the mean after 82.33 and the p-value is 0.00, it can be concluded that there is an effect of providing video education on parental knowledge on preventing diarrhea in toddlers at the Lubuk Sanai Health Center, Mukomuko Regency in 2022. Suggestions in this study are expected for researchers who are expected to be able to use other research variables that are more specific by looking at the influence of variables such as work, age and experience of the mother and increasing the number of samples.